The Barriers of Implementing E-Tendering System By Quantity Surveyors in Selangor - Chong, Won Jiun (2016)
Nowadays, the trends of construction is growing up rapidly where the time saving and cost efficiency arc the main considerations to all the construction players and others. However, the most common practice of tendering process in Malaysia is still based on the conventional method despite there are many benefits of using H-tendering system. The aim of this thesis is to identify and investigate the barriers of implementing E4cndering system by Quantity Surveyors in Selangor, and to produce recommendations for improving the use of H-tendering system as well. First, the possible barriers of implementing E-tender arc identified by reviewing the related research and information from others. This is followed by the investigation of the barriers as aforesaid through an online survey and the results are used for data analysis in order to find out the few main barriers of implementing H-tendering system. Besides, the rank correlation and T-test are being used in the data analysis part as well. Based on the results, there are still many of Quantity Surveyors prefers to proceed the tendering process by using traditional method instead of using E-tender. Nevertheless, most of them shows that they are willing to use E-tender in the near future.